Biblical Polish and its rhetorical background — research proposals - Koziara, Stanisław (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article deals with selected issues of biblical Polish seen as one of the stylistic varieties of the Polish language. The main aim of the study is to indicate the possibility of widening the hitherto attempts to describe this thematic domain of Polish language by means of approaches referring to the methods of rhetorical analysis originating both from the Hellenic and Semitic rhetorical tradition. The author has presented the application of such a research procedure on the basis of a selected sample of materials, including fixed units of Polish language of the phraseological and paremiological biblical type as well as wider textual sequences.